Autoxidation von CuI-Komplexen, II: Mechanismus der Autoxidation von Komplexen mit einzähnigen Stickstoffliganden - A. Zuberbühler (CHIMIA)
The autoxidation of cuprous complexes with monodentate nitrogeneous bases (L) has been studied spectrophotometric-ally and by following the O2-consumption with an oxygen sensor. The proposed mechanism includes two different oxygenated species. CuL2O2+ is less reactive than CuL3O2+ by many powers of magnitude which is explained by the fact that  CuL2O2+ has a coordination number of 3, specific for CuI, whereas CuL3O2+ may gain quasiplanar, CuII specific, symmetry by molecular vibration.